(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Recent years have seen emergence of platform as the dominant organizational form with firms competing as ecosystems of consumers, partners and suppliers.The ability of firms to build multi-sided platform with ability to attract consumers and complementors is critical to growth and survival of the firms. These ecosystems are socio-technical systems where the properties of the underlying technical architecture combine with human-agency.Digital platforms are “multisided digital frameworks that shape the terms on which participants interact with one another “(Kenney Zysman, 2016) and by being intermediaries platforms depend on network effects.Studies have identified generativity as the key driver of platform growth. Remneland-Wikhamn, Ljungberg, Bergquist, and Kuschel (2011) show that “it is generativity – not openness – that builds the aggregated value” and find generatively as significant to open and distributed innovation.In this study we focus on the phenomenon of generativity as viewed by the complementors in a platform context as part of this study.We develop research prepositions that form the basis for further empirical studies to develop the characteristics of the ecosystem architecture that are critical to achieve generativity